The Influence of the VR Environment on the Level of Anxiety - M.M. Marinova (Экспериментальная психология, 2022)
A technology of using virtual reality (VR) technology for psychological therapy of anxiety states is described. The technology is the relaxation computer VR-program “Ocean Rift”, which consists in the possibility of exploring the virtual underwater world and its inhabitants. Through virtual reality goggles, the observer could navigate through the sea, hear the sound of the sea, and turn and rotate their head with a 360° view. The study involved 120 subjects (74 women, 46 men) between the ages of 18 and 54 years, divided into three groups: low, moderate and high anxiety. It was shown that the relaxing effect of the virtual environment has a different effect on the severity of anxiety. For respondents with increased anxiety the method described is an effective way to relieve tension, lowering levels of situational and general anxiety and increasing positive impressions.